Efisiensi Usahatani Jagung Pipilan di Kecamatan Marang Kayu Kabupaten Kutai Kartanegara - Ida Bagus Made Agung Dwijatenaya; Astik Drianti; Eko Susilo (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
In traditional farming, production factors are generally used for generations. The factors of production used are not well measured, as a result, farming is carried out inefficiently. Another factor that causes inefficient farming is driven by social factors of farmers. This study aimed to determine the price efficiency, technical efficiency, and economic efficiency of shelled corn farming. This research was conducted in Marang Kayu District, Kutai Kartanegara Regency. Data were collected through interviews with a sample of 46 farmers. Price efficiency analysis of shelled corn farming using Cobb-Douglas function analysis. Technical efficiency analysis using frontier production function version 4.1c. Calculation of economic efficiency by calculating the multiplication between the value of price efficiency and technical efficiency (EE = EH x ET). The results showed that the price efficiency of 0.941 means inefficient, technical efficiency of 0.998 means inefficient, and economic efficiency of 0.9391 which indicates that shelled corn farming is inefficient.